Optimization of a Membrane Feeding Assay for Plasmodium vivax Infection in Anopheles albimanus. - Andrés F Vallejo; Kelly Rubiano; Andres Amado; Amy R Krystosik; Sócrates Herrera; Myriam Arévalo-Herrera (PLoS Neglected Tropical Diseases, 2016)
INTRODUCTION:Individuals exposed to malaria infections for a long time develop immune responses capable of blocking Plasmodium transmission to mosquito vectors, potentially limiting parasite spreading in nature. Development of a malaria TB vaccine requires a better understanding of the mechanisms and main effectors responsible for transmission blocking (TB) responses. The lack of an in vitro culture system for Plasmodium vivax has been an important drawback for development of a standardized method to assess TB responses to this parasite. This study evaluated host, vector, and parasite factors that may influence Anopheles mosquito infection in order to develop an efficient and reliable assay to assess the TB immunity. METHODS/PRINCIPAL FINDINGS:A total of 94 P. vivax infected patients were enrolled as parasite donors or subjects of direct mosquito feeding in two malaria endemic regions of Colombia (Tierralta, and Buenaventura). Parasite infectiousness was assessed by membrane feeding assay or direct feeding assay using laboratory reared Anopheles mosquitoes. Infection was measured by qPCR and by microscopically examining mosquito midguts at day 7 for the presence of oocysts. Best infectivity was attained in four day old mosquitoes fed at a density of 100 mosquitos/cage. Membrane feeding assays produced statistically significant better infections than direct feeding assays in parasite donors; cytokine profiles showed increased IFN-γ, TNF and IL-1 levels in non-infectious individuals. Mosquito infections and parasite maturation were more reliably assessed by PCR compared to microscopy. CONCLUSIONS:We evaluated mosquito, parasite and host factors that may affect the outcome of parasite transmission as measured by artificial membrane feeding assays. Results have led us to conclude that: 1) optimal mosquito infectivity occurs with mosquitoes four days after emergence at a cage density of 100; 2) mosquito infectivity is best quantified by PCR as it may be underestimated by microscopy; 3) host cellular immune response did not appear to significantly affect mosquito infectivity; and 4) no statistically significant difference was observed in transmission between mosquitoes directly feeding on humans and artificial membrane feeding assays.